Deep Complexity and the problem of criticality in Morin’s and Le Moigne’s accouts of complexity - Delorme, Robert (Journal of Public Governance, 2013)
The article is an attempt to determine whether the perspective of understanding complexity adopted by Edgar Morin and Jean-Louis Le Moigne involves criticality that constitutes the central tenet of Deep Complexity. First, Edgar Morin’s views on complexity and simplification are presented and then the intellectual affinity between the author of the article, his paradigm of Deep Complexity and E. Morin’s work are discussed. Subsequently, the author offers a multidimensional, critical comparison of the constitutive principles of Morin’s Method with the foundations of the paradigms of complexity and Deep Complexity. The next part of the article focuses on the achievements of Jean-Louis Le Moigne in the area of modelling complex systems and his impact on research into complexity. Final remarks review the contribution of Morin and Le Moigne to this field of study.